设平面区域 $G$ 是由直线 $y=0, x=\mathrm{e}$ 以及曲线 $y=\ln x$ 围成, 随机变量 $(X, Y)$ 在区域 $G$ 内服 从均匀分布.
(I) 求条件密度函数 $f_{X \mid Y}(x \mid y)$ 与 $f_{Y \mid X}(y \mid x)$;
(II) $F(x, y)$ 是 $(X, Y)$ 的分布函数,求 $F\left(\frac{\mathrm{e}}{2}, \ln \frac{\mathrm{e}}{2}\right)$;
(III) 设 $\left(Y_1, Y_2, \cdots, Y_n\right)$ 是取自 $Y$ 的样本, $S^2=\frac{1}{n-1} \sum_{i=1}^n\left(Y_i-\bar{Y}\right)^2$ 为样本方差, 求 $E\left(S^2\right)$.
【答案】 (I) 因 $S(G)=\int_1^e \ln x \mathrm{~d} x=1 \Rightarrow f(x, y)=\left\{\begin{array}{cc}1, & (x, y) \in G \\ 0, & \text { 其他 }\end{array}\right.$, 可得边缘密度函数:
当 $1 < x < e$ 时, $f_X(x)=\int_{-\infty}^{+\infty} f(x, y) \mathrm{d} y=\int_0^{\ln x} 1 \mathrm{~d} y=\ln x$,
所以 $f_X(x)=\left\{\begin{array}{cc}\ln x, & 1 < x < \mathrm{e} \\ 0, & \text { 其他 }\end{array}\right.$.
当 $0 < y < 1$ 时, $f_Y(y)=\int_{-\infty}^{+\infty} f(x, y) \mathrm{d} x=\int_{e^y}^e 1 \mathrm{~d} x=\mathrm{e}-\mathrm{e}^y$,
所以 $f_Y(y)=\left\{\begin{array}{cc}\mathrm{e}-\mathrm{e}^y, & 0 < y < 1 \\ 0, & \text { 其他 }\end{array}\right.$.
当 $0 < y < 1$ 时, $f_{X \mid Y}(x \mid y)=\frac{f(x, y)}{f_Y(y)}=\left\{\begin{array}{cc}\frac{1}{e-\mathrm{e}^y}, & \mathrm{e}^y < x < \mathrm{e} \\ 0, & \text { 其他 }\end{array}\right.$,
当 $1 < x < \mathrm{e}$ 时, $f_{Y \mid X}(y \mid x)=\frac{f(x, y)}{f_X(x)}=\left\{\begin{array}{cc}\frac{1}{\ln x}, & 0 < y < \ln x \\ 0, & \text { 其他 }\end{array}\right.$.
(II) $F\left(\frac{\mathrm{e}}{2}, \ln \frac{\mathrm{e}}{2}\right)=\int_{-\infty}^{\frac{\epsilon}{2}} \int_{-\infty}^{\ln \frac{\mathrm{t}}{2}} f(x, y) \mathrm{d} x \mathrm{~d} y=\int_1^{\frac{\epsilon}{2}} \mathrm{~d} x \int_0^{\ln x} 1 \mathrm{~d} y=\frac{\mathrm{e}}{2} \ln \frac{\mathrm{e}}{2}-\frac{\mathrm{e}}{2}+1=1-\frac{\mathrm{e}}{2} \ln 2$.
(III) $E(Y)=\int_{-\infty}^{+\infty} y f_Y(y) \mathrm{d} y=\int_0^1 y\left(\mathrm{e}-\mathrm{e}^y\right) \mathrm{d} y=\frac{1}{2} \mathrm{e}-1$,
$E\left(Y^2\right)=\int_{-\infty}^{+\infty} y^2 f_Y(y) \mathrm{d} y=\int_0^1 y^2\left(\mathrm{e}-\mathrm{e}^y\right) \mathrm{d} y=2-\frac{2}{3} \mathrm{e}$
$D(Y)=E\left(Y^2\right)-[E(Y)]^2=2-\frac{2}{3} \mathrm{e}-\left(\frac{1}{2} \mathrm{e}-1\right)^2=1+\frac{1}{3} \mathrm{e}-\frac{1}{4} \mathrm{e}^2$, 所以,
$E\left(S^2\right)=D(Y)=1+\frac{1}{3} \mathrm{e}-\frac{1}{4} \mathrm{e}^2$.


系统推荐